Investigating cognitive impairment, biopsychosocial barriers, and predictors of return to daily life among older stroke survivors - Björck, Alexandra; Matérne, Marie; Arvidsson Lindvall, Mialinn; Jarl, Gustav (Frontiers in Neurology, 2024)
Abstract Purpose: The aim was to investigate the associations between cognitive impairment and biopsychosocial factors among older stroke survivors and predictors of poststroke return to daily life. Materials and methods: This cross-sectional study involved 117 stroke survivors (61% men) with an average age of 77 years (range 65-91). The participants completed two questionnaires (Riksstroke and Short Form 36 questionnaires). The Montreal Cognitive Assessment (MoCA) was used to assess cognitive abilities. The International Classification of Functioning, Disability, and Health (ICF) framework guided the selection of biopsychosocial variables. We used Spearman's correlation coefficient and multiple logistic regression in the analyses. Results: The average MoCA score was 21.7 points (range: 4 to 30, SD 5.6). The need for assistance from relatives and professionals, need for help with dressing and household chores, reliance on others for mobility, and reading and balance problems were correlated with more severe cognitive impairment (r=0.20-0.33). Cognitive impairment, fatigue, and balance issues predicted an unfavourable return to daily life (odds ratio: 6.2-6.8). Conclusion: The study indicated that cognitive impairment is associated with difficulties in all ICF domains. Cognitive impairment, fatigue, and balance issues are associated with an unsuccessful return to daily life. Prioritizing these factors and screening for cognitive impairment with objective assessment tools may improve rehabilitation outcomes and enhance overall quality of life poststroke.